Go, cub! - Neuman, Susan B. (Washington, D.C. : National Geographic, 2014)
Join the little lion cub on his day of adventures on the African savanna. Watch him run, jump, play, eat, and sleep, cuddle with mom, and roll around with his brother and sister. Told in simple yet lively text built with sight words and using picture icons to aid reading.
"Ready to read"--Page [4] of cover.
10
Keywords: Lion -- Infancy -- Juvenile literature; Animals -- Infancy -- Juvenile literature